Exploring the Types and Causes of Pauses in Students' English Oral Presentations - Idris, Wiranto (Universitas Negeri Gorontalo, 2024)
This study examines the types and causes of pauses in students' English presentations at a Senior High School in Gorontalo, Indonesia, with a focus on understanding how pauses affect fluency in public speaking. Drawing on Schroeder and Sonderegger (2014), the study explores the relationship between pause occurrence and speech rate in both spontaneous dialogues and read speech. The study provides insights into how pauses function in natural speech and the factors that influence their frequency and type. Specifically, it categorizes pauses into two primary types: silent pauses and filled pauses. This research analyzes the frequency and nature of pauses during classroom presentations. The study involved ten 12th-grade students, who were observed during their presentations, with data collected through audio recordings, questionnaires, and direct observations. The findings revealed a total of 84 pauses, with 45 silent pauses and 39 filled pauses. Silent pauses were more frequent, often resulting from students struggling to recall words or organizing their thoughts. The study identified several factors contributing to pauses, including nervousness, concerns about grammar, and lack of vocabulary. The results suggest that pauses are not only a natural aspect of speaking but also indicative of underlying psychological and linguistic challenges. This research has implications for language instruction, highlighting the importance of addressing anxiety, improving vocabulary, and reinforcing grammar to help students enhance their fluency and confidence in public speaking.